Technology Transfer in Developing Countries and Its Relationship with Human Resources Development - Ellitan, Lena (Jurnal Ilmiah Ranggagading (JIR), 2006)
The present concern with technology transfer is not a new one. To date, technology transfer is an important issue, discussed in any meeting held between developing and developed countries. Therefore, it is not exaggeration to say that the economic growth of every nation inextricable linked to the successful international transfer of technology. This paper is an attempt to discuss about the relationship between technology transfer and human resource development. It is due to technology transfer usually requires training to increase the skills and abilities of human resource in developing countries. Technology transfer requires training but the technology receiver will never catch up with the provider if the training is inefficient or ineffective. Therefore, the key issue of technology transfer is how to establish the methods of learning technology and change the system of thinking of the trainees. Moreover, the degree of technology transfer is interrelated with the attitude of trainees. The trainees must play an important role during the process of technology transfer so that the technology transferred can take root and be generated. Keywords: Technology Transfer; Human Resources Development.